Re-centering social justice in conservation science: Progressive policies, methods, and practices - Montgomery, Robert A.; Kabra, Asmita; Kepe, Thembela; Garnett, Stephen; Merino, Roger (Biological conservation, 2024)
From the inception of the field itself, conservation biology has been described as a mission-driven discipline. While the mission orientation has been aligned to protect and recover biodiversity, the manner in which conservation practice has been implemented has, at various times and in various places, come at a cost to the basic rights of local people. With multi-national commitments aiming to expand protected areas both in number and size, there is the potential for human rights violations to also rise. Importantly, biodiversity conservation and human rights are not incompatible spheres. Herein, both ecological and social values can be integrated to reshape conservation science and increase the efficacy of the discipline's applied practices. To do so, however, the social justice dimensions must be highlighted and amplified and various methods, techniques, and applied practices to uplift local people in conservation, must necessarily be incorporated. To this end we have edited a Special Issue in Biological Conservation called “The Central Importance of Social Justice in Conservation.” Here, we discuss the reasons why social justice is integral to effective conservation practice. We then briefly highlight the impressive work being performed around the world to embed principles of social justice within the fabric of progressive conservation practice. Exploring case studies of emergent techniques and methods to conserve biodiversity and improve the well-being of local human communities, we conclude by discussing how the integrity of coupled human and natural systems requires conservation practice that facilitates the protection of biodiversity via the promotion of human social justice.